1995
DOI: 10.1002/prot.340230206
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic folding and unfolding of staphylococcal nuclease and its six mutants studied by stopped‐flow circular dichroism

Abstract: Kinetics of refolding and unfolding of staphylococcal nuclease and its six mutants, each carrying single or double amino acid substitutions, are studied by stopped-flow circular dichroism measurements. A transient kinetic intermediate formed within 10 ms after refolding starts possesses a substantial part of the N-domain core beta-structure, whereas helices are formed at the later stages. The structure of the kinetic intermediate is less organized than the structure that is known to be formed by a nuclease 1-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
22
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 47 publications
12
22
0
Order By: Relevance
“…The global rates of 5 sec −1 and 0.13 sec −1 observed in our time‐resolved labeling experiments are consistent with similar rates detected by other methods (Sugawara et al 1991; Chen and Tsong 1994; Kalnin and Kuwajima 1995; Maki et al 1999; Walkenhorst et al 1997). There appears to be no detectable protection of amides associated with a 1‐sec −1 phase observed by stopped flow, which is consistent with our assignment of this phase to a nonproline cis ‐ trans isomerism in our previous stopped‐flow fluorescence studies (Walkenhorst et al 1997).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The global rates of 5 sec −1 and 0.13 sec −1 observed in our time‐resolved labeling experiments are consistent with similar rates detected by other methods (Sugawara et al 1991; Chen and Tsong 1994; Kalnin and Kuwajima 1995; Maki et al 1999; Walkenhorst et al 1997). There appears to be no detectable protection of amides associated with a 1‐sec −1 phase observed by stopped flow, which is consistent with our assignment of this phase to a nonproline cis ‐ trans isomerism in our previous stopped‐flow fluorescence studies (Walkenhorst et al 1997).…”
Section: Discussionsupporting
confidence: 91%
“…More recently, several lines of study, including calorimetry (Carra et al 1994; Carra and Privalov 1995 Carra and Privalov 1996), NMR (Wang and Shortle 1995; Gillespie and Shortle 1997), pulsed hydrogen exchange (Jacobs and Fox 1994), mutational studies (Kalnin and Kuwajima 1995), and kinetic analysis of a proline‐free (Pro − ) SNase variant (Walkenhorst et al 1997) have converged to indicate that the β‐sheet subdomain of the protein is the most stable to denaturation and among the first regions of the protein to fold. By coupling hydrogen exchange labeling techniques with NMR detection of individual amide protons, it is possible to localize folding events to specific regions of the protein (Roder and Wüthrich 1986; Roder et al 1988; Udgaonkar and Baldwin 1988).…”
mentioning
confidence: 99%
“…Mutation analysis revealed that Val66, Ala69 and Ala90 in the β-barrel domain are fully native-like in the transition state. 41 In contrast, a Ca 2+ -binding site, which is located at the interface of theβ-barrel and the α-helical domains, is not yet formed at this state. 43 These findings indicate that the final steps of folding involve formation of specific docking interactions between the subdomains of SNase.…”
Section: Introductionmentioning
confidence: 93%
“…Similar results have been obtained for a number of other proteins including α-lactalbumin [78] and apomyoglobin [79], giving rise to the proposal that the folding process proceeds via an intermediate with the principal characteristics of a "molten globule" (see Section 4.2). In a study of the refolding of native and mutant forms of staphylococcal nuclease, it was found that a transient kinetic intermediate formed within 10 msec [80]. This intermediate possessed only about 30% of the native ellipticity at 225 nm; in conjunction with hydrogen exchange experiments it was shown that this relatively low amplitude reflected formation of the 5-stranded β-sheet structural core of the N-terminal domain of the enzyme, with the helices (which contribute the bulk of the CD signal at 225 nm) formed at a later stage [81].…”
Section: The Nature Of Early Folding Intermediatesmentioning
confidence: 99%